The effect of selenium on antioxidant system in aquaculture animals - Li, Zi-Meng; Wang, Xiu-Li; Jin, Xiao-Min; Huang, Jia-Qiang; Wang, Lian-Shun (Frontiers in Physiology, 2023)
With the increasing intensification of modern aquaculture, some adverse conditions, such as crowding stress, hypoxia, and malnutrition will be generated in the process of fish farming, which will easily lead to oxidative stress. Selenium (Se) is an effective antioxidant, participating and playing an important role in the antioxidant defense system of fish. This paper reviews the physiological functions of selenoproteins in resisting oxidative stress in aquatic animals, the mechanisms of different forms of Se in anti-oxidative stress in aquatic animals and the harmful effects of lower and higher levels of Se in aquaculture. To summarize the application and research progress of Se in oxidative stress in aquatic animals and provide scientific references for its application in anti oxidative stress in aquaculture.